##### Verify a-(-b)= a + b for the following values of a and b:(i) a = 21, b = 18(ii) a = 118, b = 125(iii) a = 75, b = 84(iv) a = 28, b = 11

(i) We have given in the question that,

a = 21

b = 18

We have to prove that:

a – (-b) = a + b

Now,

a – (-b) = 21 – (-18)

= 21 + 18

= 39

Also,

a + b = 21 + 18

= 39

Therefore,

a – (-b) = a + b

Hence, verified

(ii) We have given in the question that,

a = 118

b = 125

We have to prove that:

a – (-b) = a + b

Now,

a – (-b) = 118 – (-125)

= 118 + 125

= 243

Also,

a + b = 118 + 125

= 243

Therefore,

a – (-b) = a + b

Hence, verified

(iii) We have given in the question that,

a = 75

b = 84

We have to prove that:

a – (-b) = a + b

Now,

a – (-b) = 75 – (-84)

= 75 + 84

= 159

Also,

a + b = 75 + 84

= 159

Therefore,

a – (-b) = a + b

Hence, verified

(iv) We have given in the question that,

a = 28

b = 11

We have to prove that:

a – (-b) = a + b

Now,

a – (-b) = 28 – (-11)

= 28 + 11

= 39

Also,

a + b = 28 + 11

= 39

Therefore,

a – (-b) = a + b

Hence, verified

13